De la “tierra del futbol” a la “tierra de los megaeventos”: una evaluación de la modernización de los estadios brasileños bajo la perspectiva de los seguidores organizados de São Paulo - Buarque de Hollanda, Bernardo; Medeiros, Jimmy (El Colegio de México, A.C., 2022)
This article aims to assess the so-called “legacy” of the 2014 fifa World Cup in Brazil through an analysis of the period following this event. It examines the relationship between the new arenas and the fans, particularly those known as the torcidas organizadas. It opens by describing the architectonic and infrastructural transformations that were carried out for the World Cup, reviews the literature on how fans have used and occupied these new stadiums and concludes with a survey of fans in São Paulo in the wake of the World Cup. This survey allows for the identification of the positive and negative aspects of the new athletic facilities as mentioned by their users, distinguishing between the modernization of stadiums to meet fifa standards and their a posteriori uses, particularly the so-called celebrations in the stands –banners, flags, songs and dances– during state and national championships. Through “clubism” in soccer –a way of supporting a club that differs from the way in which one supports the national team– the article concludes with the heterogeneous, differing perspectives of the members of the torcidas organizadas.